Suggestopedia and Students' Motivation: Speaking Class - Deswarni, Dini; Zainil, Yetti; Syarif, Hermawati (Universitas Muhammadiyah Surakarta, 2023)
The research investigates the impact of the Suggestopedia method on student motivation in speaking classes. Suggestopedia is an innovative teaching method designed to increase student engagement and motivation in the classroom, particularly in the area of communication skill development.. The method is predicated on the notion that students have untapped resources that can be accessed through suggestive learning strategies. Suggestopedia's goal in speaking classes is to reduce anxiety and increase students' confidence in verbal expression. Learners are encouraged to take risks, make mistakes, and develop their speaking abilities as a result of the method's supportive environment. Positive reinforcement and suggestion play a significant role in Suggestopedia, contributing to the increased motivation and engagement of students. Integrative and instrumental motivations are also investigated in the context of acquiring a foreign language, with an emphasis on the cultural and pragmatic aspects of language acquisition. Ten students from the first semester of the English Department at STAI Hubbulwatahan Duri Riau were interviewed using qualitative methods, such as focus group discussions, to obtain in-depth insights. The findings indicate that participants highly value the motivational aspects of Suggestopedia, such as its impact on interest, social contact, cultural awareness, and speaking skills. While some participants held pessimistic views regarding practical motivations, the majority acknowledged the significance of English proficiency for personal and professional development. Overall, the study indicates that Suggestopedia can motivate in language learning, and that integrating integrative motivation into language teaching strategies, particularly in English-speaking classrooms, can produce positive results.